Phylogenetic footprints in organizational behavior - Witt, Ulrich; Schwesinger, Georg (Papers on economics and evolution, 2012)
An evolutionary tool kit is applied in this paper to explain how innate social behavior traits evolved in early human groups. These traits were adapted to the particular production requirements of the group in human phylogeny. They shaped the group members' attitudes towards contributing to the group's goals and towards other group members. We argue that these attitudes are still present in modern humans and leave their "phylogenetic footprints" also in present-day organizational life. We discuss the implications of this hypothesis for problems arising in firm organizations in relation to the coordination and motivation of organization members. -- evolution ; pre-adaptations ; group selection ; firm organization ; organizational behavior ; leadership
Keywords: Arbeitspapier; Graue Literatur